Do big 4 auditors improve the ability of goodwill to forecast future cash flows? the Malaysian evidence - Al-Hiyari, Ahmad; Abdul Latif, Rohaida; Amran, Noor Afza (Virtus interpress, 2016)
The accounting rules prescribed in Malaysian Financial Reporting Standard (MFRS) 3, Business combination, and (MFRS) 136, Impairment of Assets, give managers considerable reporting discretion in allocating goodwill and estimating its actual value. Agency theory predicts that managers may use the accounting discretion granted by the new rules to pursue their own interests at the expense of shareholders.Hence, auditors are required to exercise professional judgement when investigating hard-to-verify management assumptions and valuations.We exploit this issue by examining whether predictive ability of goodwill improved in the presence of Big 4 auditors. We provide evidence that goodwill has a significant predictive ability for second and third-year ahead cash flows which exists only in the firms audited by the large international reputable accounting firms.This suggests that Big 4 auditors play an important role in ensuring appropriate implementation of the present accounting for goodwill.